PENGARUH PENERAPAN APLIKASI “BIDANKU” TERHADAP PENINGKATAN PENGETAHUAN DAN EFIKASI DIRI IBU NIFAS - Farhati Farhati; Yulia Ulfah Fatimah; Chris Sriyanti (Poltekkes Kemenkes Bandung, 2023)
The postpartum period is a critical period for the mother, approximately 60% of maternal deaths occur after delivery, and 50% of postpartum deaths occur within the first 24 hours of labour. This period is an important transitional period, but in women's health care, it is an aspect that is often neglected. Preparations for the puerperium that have not been given since pregnancy have caused mothers not to know how to properly care for themselves and their babies. One of the bridges to optimize postnatal education efforts is through the development of the